Flexibility, trade-offs and learning in manufacturing system design. (1st January 2000) - Slack, Nigel
Three independent case-based research projects are examined, using similar methodologies, so as to understand the relationships between the nature of each manufacturing system's redesign, their strategic context, the assessment of each system's flexibility, their managers' perceptions of the trade-offs involved in the design and the degree of organisational learning. A model is proposed which suggests an interplay between three related sets of activities. These are a "structuring" activity, a "suppositional" activity and an "assimilation" activity. Parallels are drawn between these studies and other work on learning and technological competence.